Touch Operation of the Electronic Calculator - Jones, Arvella (Thomson Learning, 2005)
Like the previous edition, after only ten 55-minute sessions, users will become proficient touch-method operators of any calculator or microcomputer with a ten-key pad. A valuable supplement in accounting, record keeping, business math, and other classes where calculators or computers are used